Cashless Society dan Perubahan Pola Pengeluaran Generasi Z di Kota Metro - Fika Rahma Dhania; Upia Rosmalinda; Hermanita Hermanita (Economic Reviews Journal, 2026)
The development of digital financial technology has led to the emergence of a cashless society, where non-cash transactions are increasingly used in daily activities, but have the potential to increase consumer behavior. Various payment platforms such as e-wallets, internet banking, and SeaBank have been integrated with QRIS, enabling easy and efficient transactions. This study aims to analyze the use of cashless payment systems and their impact on Generation Z spending patterns in Metro City. The method used was a descriptive qualitative approach through interviews with Generation Z and cafe owners. The results show that QRIS has become the primary payment method due to its convenience and speed. This condition increases transaction frequency and encourages spontaneous purchases. Some informants experienced increased spending, while others only monitored transactions without consistent control. Thus, the use of QRIS provides convenience, but has the potential to increase consumer behavior without good financial management.